Training as a method of preventing negative mental states of young schoolboys (Actual Problems of Psychology in Educational Institutions, 2018)
The article envisages the efficiency of implementation oftraining program aiming at the prevention negative mental states. It is noted thatmental states are very important in the life of modern primary school ageсhildren. The focused on the fact that a trainings are very different. The resultsof the research are analyzed and the structure and level of negative mental statesat students of primary school age. The analyzed training as a way of preventionof negative mental states at students of primary school age.
Keywords: training, mental states, younger students, prophylaxis